METHODOLOGY FOR TEACHING STUDENTS NATIONAL INSTRUMENTS IN CIRCLE TRAINING. - Abduraimov Sherzod Zokir o`g`li (TADQIQOTLAR.UZ, 2024)
Annotation. This article presents a methodology for effectively teaching students National Instruments (NI) technology through a circle training approach. Circle training integrates theoretical knowledge with practical application, fostering a deeper understanding and skill development among students. By incorporating this methodology, educators can optimize student engagement and proficiency in utilizing National Instruments tools for various engineering applications.